Geert Goiris : lying awake. - Goiris, Geert; van Duijvenboden, Nickel; Vollgraff, Matthew; Willems, Roger; Exhibition. Leuven. Museum M 2013-2,14 (Amsterdam : Roma, 2013)
The work of Belgian artist and photographer Geert Goiris straddles a liminal position between landscape and still life. Haunting and dreamlike, the sometimes alien images denote a fundamental tension between man and nature often bordering on the sublime. From seemingly composed scenes of various objects or portraits to architectural and natural landscapes, the images impart a sense of uncanny timing or discerning observation, achieving both qualities of suspended time and unspoken narrative. Included is 'Myths, Places and Protagonists', a collection of short texts by Goiris offering personal insight into how a number of the images came to be created or inspired. 0Exhibition: M-Museum, Leuven, Belgium (14.2.-19.5.2013).
Published coinciding with the exhibition from 14.02 till 19.05.2013
boek
Keywords: Exhibitions -- Tentoonstellingen -- Expositions; Goiris, Geert